(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
Rice production is affected by important pathogens such as Magnaporthe oryzae, Cochliobolus miyabeanus, Monographella albescens and Sarocladium oryzae, and orchid mycorrhizal fungi can contribute to the biocontrol of these diseases. The aim of this study was to characterize the antagonism mechanisms of W. circinata against rice pathogens. The indoleacetic acid (IAA) and lytic enzymes of W. circinata were quantified. The effectiveness of the bioagent and its metabolites was assessed in vitro. Antagonism in vivo against rice blast was also investigated. Waitea circinata produced IAA (2.3 µg ml-1), cellulase and polyphenol oxidase in a qualitative test. Glucanase, chitinase and protease were also produced in culture with cell walls and in co-culture with pathogens to explain antibiosis. W. circinata acts on direct antagonism by antibiosis and volatile metabolites. Mycelial suspension reduced M. oryzae conidial germination, appressorium formation, and rice blast by 61, 82 and 84%, respectively. W. circinata, a unique bioagent, controls four rice pathogens. The results could contribute to new formulations containing this fungus, enzymes as well as its volatile metabolites.